Could Cariprazine Be a Possible Choice for High Functioning Autism? A Case Report - Andrea Miuli; Carlotta Marrangone; Ornella Di Marco; Arianna Pasino; Gianfranco Stigliano; Alessio Mosca; Mauro Pettorruso; Fabrizio Schifano; Giovanni Martinotti (MDPI AG, 2023)
This case report was conducted by searching for the following keywords on PubMed: High Functioning Autism, Autism Spectrum Disorder, cariprazine, aripiprazole, partial agonist antipsychotic, DRD2/DRD3. High Functioning Autism (HFA) is a neurodevelopmental disorder characterized by the core symptoms of autism spectrum disorder (ASD) with average intellectual abilities, behavioral symptoms such as irritability, hyperactivity, aggressiveness and mood symptoms. HFA is not a term used in the Diagnostic and Statistical Manual of mental disorders (DSM), but it is commonly used to identify patients diagnosed with Autistic Disorder (AD) or Pervasive Developmental Disorder-Not Otherwise Specified (PDD-NOS) with average or above average intellectual abilities. Several factors are involved in HFA development, including environmental and genetic factors. In particular, over the last several decades, dopaminergic signaling system dysfunction has been highlighted as being responsible for behavioral patterns. Nowadays, symptoms of ASD lack a specific pharmacological treatment. The only medications approved by the Food and Drug Administration (FDA) for symptoms associated with ASD, in particular the irritability, are risperidone and aripiprazole. According to the hypothesis that dopamine receptor DRD2 and DRD3 might be involved in impulsive behavior, stereotypy, repetitive behaviors and language impairment, cariprazine could be a therapeutic option. This molecule is primarily characterized by DRD3 partial agonism and serotonin 5-HT1A partial agonism, with a lower ability to activate DRD2 than other third-generation antipsychotics, such as aripiprazole. We have reported here a case study of treatment of HFA with cariprazine.